Preliminary Design for Orthodontic Bracket Holder - Sadiq Jafer Hamandi; Harraa S. Mohammed-Salih; Faten Abdulameer Ali (مجلة النهرين للعلوم الهندسية)
The process of placing the brackets in their proper positions in the field of orthodontics is consider one of the main steps in orthodontic treatment. In order to achieve high accuracy placements for the brackets, many methods are available today, starting from direct and indirect methods, each of them has advantages and disadvantages regarding the accuracy and the time for patient treatment. In this study, a new mechanism is introduce with its mechanical behavior in order to reduce the time required for patient treatment and to increase the accuracy for bracket placements. The newly mechanism was designed using Solidworks CAD software with a total Virtual functionality for all of the parts of the assembly, then a simulation was carried out to find the stress distribution, deformation, and strain on the main parts of the proposed assembly. The finished design shows a high precision mechanism that is able to place brackets one by one on the teeth.